Spectral and Temporal Properties of CXOUJ122956.7+075728 (ULX-1), an Ultraluminous X-Ray Source in NGC 4472 - Devi, A. Senorita (East European Journal of Physics, 2024)
This report presents a comprehensive analysis of the spectral and temporal characteristics of a highly significant Ultraluminous X-ray Source (ULX) designated as CXOUJ122956.7+075728 (ULX-1) situated in the elliptical galaxy NGC 4472 within the Virgo cluster. ULX-1 exhibits a soft spectral state, featuring a cool accretion disk component with kTin ∼ 0.15 keV, accompanied by a power-law tail displaying a steep power-law photon index, Γ ∼ 2.8. The spectral findings strongly support an estimated black hole mass of approximately 3.30 × 103 M⊙ under an isotropic emission model, and around 1.47 × 103 M⊙ in an extreme beaming scenario. Temporally, ULX-1 displays significant variability on time scales of 0.5, 1, and 2 ks, suggesting the possibility of instabilities within the accretion disk contributing to this behavior. However, despite this temporal variability, the power spectra analysis of this soft ULX reveals no signatures of pulsations, distinguishing it from certain pulsating ULXs (PULXs) typically associated with neutron stars. This absence of pulsations in ULX-1 further underscores its unique spectral and temporal characteristics within the broader context of ULX phenomena.